2017
DOI: 10.3389/fpsyg.2017.00874
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diaphragmatic Breathing on Attention, Negative Affect and Stress in Healthy Adults

Abstract: A growing number of empirical studies have revealed that diaphragmatic breathing may trigger body relaxation responses and benefit both physical and mental health. However, the specific benefits of diaphragmatic breathing on mental health remain largely unknown. The present study aimed to investigate the effect of diaphragmatic breathing on cognition, affect, and cortisol responses to stress. Forty participants were randomly assigned to either a breathing intervention group (BIG) or a control group (CG). The B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
221
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(272 citation statements)
references
References 81 publications
10
221
2
9
Order By: Relevance
“…Previously described γ synchrony between areas of the brain as a dynamical mechanism for the control of cross-areal information flow or "communication through coherence" 3,46,47 , could be part of a larger phenomenon which includes respiratory modulations. The strong modulation of the electrocortical activity by the respiratory rhythms could be the foundation of the effect of breathing on critical functions such as cognition, affection and stress responses 34,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously described γ synchrony between areas of the brain as a dynamical mechanism for the control of cross-areal information flow or "communication through coherence" 3,46,47 , could be part of a larger phenomenon which includes respiratory modulations. The strong modulation of the electrocortical activity by the respiratory rhythms could be the foundation of the effect of breathing on critical functions such as cognition, affection and stress responses 34,49 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, deep breathing is a central element for singing, which can impact on both physiological (e.g. cardiovascular and autonomic nervous system) and emotional functions (Busch et al, 2012;Ma et al, 2017;Russo et al, 2017). Further, studies found that group singing can reduce pain threshold and pain perception (Dunbar, Baron, et al, 2012;Dunbar, Kaskatis, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…During this week, we also reviewed the sleep diary to con rm any necessary sleep changes (i.e., adjustments to the time both in and out of bed.) The diaphragmatic breathing technique promotes muscle relaxation, better breathing performance, and memory relaxation [37]. It also was especially emphasized for those who were not able to relax.…”
Section: Interventionsmentioning
confidence: 99%